DIFFERENTIATION OF TASKS IN THE PROCESS OF GRAPHIC COMPETENCE FORMATION OF HIGHER SCHOOL STUDENTS BY MEANS OF COMPUTER-ORIENTED TECHNOLOGIES - Uruskyi, Andrii; Havryshchak, Halyna (Educological discourse, 2022)
It is proposed to use differentiated tasks during drawing the parts (products) using computer-based teaching means for individual educational and research tasks (IERT). It is effective to use KOMPAS-3D (CorelDraw) for making design documentation of details (products). An exploratory research is described to identify difficulties and further interest of 1st and 2nd year students during doing the ITRT. It is established that students are not only interested in performing tasks of this type, but they also try to make changes (adjustments) to the drawings. It is noted that the use of differentiated tasks in the execution of drawings of parts (products) with computer-based teaching means helps to take into account the individual characteristics of students and the implementation of an individual approach to them. It is substantiated that while making differentiated tasks, it should be taken into account the features of computer-based teaching means with which students work, as well as the level of their mastery of this program. It is suggested to divide ITRT into two blocks: the basic - performance of the drawing construction according to the instruction; additional - performance of additional 2 tasks. The task of the additional block is offered – "To make changes to the design of the stand" and "To make a pattern, emblem or logo on the details (parts) of the product". The essence of additional tasks is described. The specifics of each of the additional tasks are also indicated.